Measured temporal parameters - Shah, Asadullah; Bhatti, Zeeshan (IIUM Press, 2011)
Speech communication is often realised by two ways monologue and dialogue modes. The temporal (time) attributes, such as active and non-active parts of both of these varies because of the nature of the modes. In monologue modes of speech communication activity of each user remains 80% and 20% are the silences and in dialogue (conversational) modes it is 40% and 60% respectively. The temporal attributes and properties of both speech communication modes can be utilised for better bandwidth efficiency. These chapters a statistical data regarding these activities for both modes are provided